EVALUASI PROGRAM PEMBERDAYAAN UMKM (JIANA ( Jurnal Ilmu Administrasi Negara ), 2020)
Evaluation, Program, Empowerment, UMKM. This research is motivated by the large number of people who open businesses in various fields but these businesses have not yet reached the point of success. This is the homework for the government in this case the Maharatu village to act and find solutions so that the problem can be resolved. The purpose of this study is to evaluate the problems faced in the UMKM community empowerment program in the Maharatu Village and what are the factors that hinder the UMKM community empowerment program in the Maharatu Village. This research uses a descriptive qualitative research method approach. Perimer data was obtained directly through interviews from informants, namely Maharatau Village Chief Krisna Minang along with staff and Chairperson of UEK-SP Lyaniza Ika Rizki. The results of this study indicate that the implementation of the Community Empowerment Program Evaluation in the UMKM Economy in the Village of Maharatu Pekanbaru City has not yet achieved the expected results, where in the implementation of UMKM empowerment there are still many business ventures that have not yet been found to be fully successful.